2019
DOI: 10.3389/fmech.2019.00052
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cylinder Deactivation and Cylinder Cutout via Flexible Valve Actuation on Fuel Efficient Aftertreatment Thermal Management at Curb Idle

Abstract: Cylinder deactivation (CDA) and cylinder cutout are different operating strategies for diesel engines. CDA includes the deactivation of both the valve motions and the fuel injection of select cylinders, while cylinder cutout incorporates only fuel injection deactivation in select cylinders. This study compares diesel engine aftertreatment thermal management improvements possible via CDA and cylinder cutout at curb idle operation (800 RPM and 1.3 bar BMEP). Experiments and analysis demonstrated that both CDA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…, using CDA and cylinder cutout at 800 r/min and 1.3 bar BMEP, per Figure 19. 20 One such CDA strategy has two (of six) CF and does not depend on exhaust manifold pressure control for improved stay-warm performance. The cylinder cutout strategy utilizes three (of six) CF, while the remaining cylinders transmit non-combusted charge gas, and requires exhaust manifold pressure control for improved stay-warm performance and EGR delivery control.…”
Section: Experimental Results For Zonementioning
confidence: 99%
See 3 more Smart Citations
“…, using CDA and cylinder cutout at 800 r/min and 1.3 bar BMEP, per Figure 19. 20 One such CDA strategy has two (of six) CF and does not depend on exhaust manifold pressure control for improved stay-warm performance. The cylinder cutout strategy utilizes three (of six) CF, while the remaining cylinders transmit non-combusted charge gas, and requires exhaust manifold pressure control for improved stay-warm performance and EGR delivery control.…”
Section: Experimental Results For Zonementioning
confidence: 99%
“…Exhaust gas-to-catalyst heat transfer rate plots, where the exhaust flow corresponds to the steepness of the slope and the crossing of the zero heat transfer rate axis represents the TOT. Figure data are at 800 r/min, 1.3 bar BMEP, and corresponds to effort described in Vos et al 20 …”
Section: Experimental Results For Zonementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies by several of the authors, and others, have demonstrated the ability to raise exhaust temperatures for more efficient aftertreatment thermal management (TM) by utilizing various strategies such as maximally closing a variable geometry turbine (VGT), cylinder deactivation (CDA), intake valve modulation, and exhaust valve modulation. 2,1017…”
Section: Introductionmentioning
confidence: 99%